The long-run effects of fiscal consolidation on economic activity in the CEMAC zone - Wabo Nokam, Vivien Narcisse; Soh, Syrie Galex (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2025)
This study aims to analyze the long-run effects of fiscal consolidation on economic activity in the Economic and Monetary Community of Central Africa (CEMAC), a grouping of six countries (Cameroon, Congo, Gabon, Equatorial Guinea, the Central African Republic, and Chad) forming a monetary union. The empirical analysis of annual data from the Bank of Central African States (BEAC) over the 1987-2016 period first enabled us to identify 22 episodes of fiscal consolidations in all the CEMAC zone countries during the above-mentioned period. Secondly, by adopting the Fully Modified Ordinary Least Square (FMLOS) and the Dynamic Ordinary Least Square (DOLS) panel methods, our results show that fiscal consolidations have recessionary (Keynesian) effects on the CEMAC zone’s economy. Those effects are mainly due to fiscal consolidations that focus on reducing public expenditure.